2017
DOI: 10.1021/acs.jpcc.6b11283
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 Nanotube/Chalcogenide-Based Photoelectrochemical Cell: Nanotube Diameter Dependence Study

Abstract: We present photo-electrochemical results for anodic TiO 2 nanotube layers grown with different diameter sizes (21, 35, 56 and 95 nm) with a thickness of approx. 560 nm using a novel anodization protocol. These tube layers were utilized as highly ordered n-type conductive scaffold for the inorganic chromophore Sn-S-Se. While downscaling the nanotube diameter significantly increased the number of nanotubes per square unit (from 5.6E+09 to 7.2E+10 pcs/cm 2 ) and thus the active surface area increased as well, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 39 publications
0
12
1
Order By: Relevance
“…21 Apparently, the coupling of CdS coatings with TiO 2 nanotube layers causes a strong sensitizing effect, as shown in Fig. 2.…”
mentioning
confidence: 88%
“…21 Apparently, the coupling of CdS coatings with TiO 2 nanotube layers causes a strong sensitizing effect, as shown in Fig. 2.…”
mentioning
confidence: 88%
“…It has been reported that TiO 2 nanotube arrays exhibit higher photoelectrochemical reactivity and photocatalytic activity than most of the conventional nanoparticles, benefited from their high surface area associated with the unique hollow‐tubular and one‐dimension architecture. Because of these advantages, TiO 2 nanotube arrays show promising potential applications in many fields, such as sensors, environment remediation, solar cells, water splitting …”
Section: Introductionmentioning
confidence: 99%
“…However, the photocatalytic property of TiO 2 photocatalysts was limited by the low visible light response and rapid recombination of photogenerated carries . To overcome these problems, various strategies such as ion doping, quantum dot or dye sensitization, noble metal decoration, additional TiO 2 coating, and heterojunction structure were attempted widely and very good effects have been achieved . In these methods, anatase/rutile heterojunction structure is relative environmental friendly, low‐cost and easy to obtain, and has attracted a lot of interests of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement of the IPCE values in the UV spectral region can be ascribed to the presence of sulphur (S) within the TiO 2 nanotube layers which removed TiO 2 surface defects and thus inhibited significant charge carrier recombination. 19 , 20 , 40 , 62 , 63 The surface incorporation of S atoms occurred during the very early ALD cycles as the bare TiO 2 surface and H 2 S came into close contact for a significant time (the exposure time was 45 s). The photoresponse of the CdS/TiO 2 nanotube layers in the visible spectral region was outstanding as compared to their blank counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Conventional thin film deposition methods such as chemical vapour deposition (CVD), physical vapour deposition (PVD) or sputtering are not suitable, as the deposited material cannot reach the deepest part of the TiO 2 nanotube layers, and effective utilization of the tube interiors is disabled due to tube mouth clogging. Other attempts, using spin-coating, 19 , 20 electrodeposition, 21 , 22 and chemical bath deposition, 23 , 24 were reported to infiltrate secondary materials in the inner surface of the nanotubes, however complete infiltration of secondary materials was unfortunately constrained to a reduced number of materials.…”
Section: Introductionmentioning
confidence: 99%